‘Ulamā,’ Maṣlaḥah, and the Politics of Fatwa: The Shifting of Ali Gomaa's Fatwa Approach during the 2011 Egyptian Revolution - Sulaiman, Akhmad; Masrukhin, Mohammad Yunus; Burdah, Ibnu (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2023)
Numerous scholars have advanced the thesis that rulers in Muslim-majority countries engage ‘ulamā’ to legitimize their political authority. This assertion seems pertinent to the actions of the state mufti of Egypt, Ali Gomaa, who issued a fatwa prohibiting demonstrations during the 2011 Egyptian Revolution. Applying the scholars' thesis to Gomaa's fatwas reveals complexity, as it turns out that Gomaa revised his fatwas, particularly those related to the transition from prohibiting demonstrations to endorsing peaceful assemblies. This research aims to analyze two aspects: exploring the motivating factors behind the changes in Gomaa's fatwas and identifying the inherent substantive shifts in his fatwas. By employing Foucault's discourse theory, the study delves into Gomaa fatwas during the 2011 Egyptian Revolution, meticulously documented on digital platforms. The research findings indicate that Gomaa's shift in fatwas stems from a vested desire for his pronouncements to achieve widespread acceptance and authority among a populace that embraces protest as an expression of freedom of speech. Gomaa modifies his fatwa, transitioning from an outright prohibition of demonstrations to permitting peaceful assemblies while encouraging demonstrators to exercise restraint through a suggestive fatwa allowing for leaving Friday prayer. Gomaa has orchestrated a paradigmatic shift in his fatwa approach, moving away from interpreting demonstrations as opposition to the rulers, grounded in preserving soul and property, toward recognizing them as manifestations of free speech rooted in citizens' rights. Banyak sarjana telah mengemukakan teori bahwa penguasa di negara-negara mayoritas Muslim melibatkan ‘ulamā’ untuk melegitimasi otoritas politik mereka. Pernyataan ini tampak relevan dengan tindakan mufti negara Mesir, Ali Gomaa, yang mengeluarkan fatwa melarang demonstrasi selama Revolusi Mesir tahun 2011. Penerapan teori para sarjana ke fatwa-fatwa Gomaa mengungkap kompleksitas, karena ternyata Gomaa merevisi fatwanya, khususnya yang terkait dengan peralihan dari melarang demonstrasi menjadi mendukung demonstrasi damai. Penelitian ini bertujuan untuk menganalisis dua aspek: mengeksplorasi faktor-faktor motivasi di balik perubahan fatwa Gomaa dan mengidentifikasi pergeseran substantif yang melekat dalam fatwanya. Dengan menggunakan teori wacana Foucault, studi ini menunjukkan bahwa pergeseran fatwa Gomaa berasal dari keinginan yang kuat agar pengumumannya diterima secara luas dan memiliki otoritas di kalangan masyarakat yang mendukung protes sebagai bentuk ekspresi kebebasan berbicara. Gomaa memodifikasi fatwanya, beralih dari larangan demonstrasi secara mutlak menjadi mengizinkan pertemuan demontrasi yang damai, sambil secara bersamaan mendorong para demonstran untuk menahan diri melalui fatwa yang mengizinkan meninggalkan salat Jumat. Gomaa mengatur pergeseran paradigma dalam pendekatan fatwanya, yakni dari menjauhi interpretasi demonstrasi sebagai bentuk perlawanan terhadap penguasa berdasarkan konsep pemeliharaan jiwa dan properti, menuju pemahaman bahwa demonstrasi adalah manifestasi kebebasan berpendapat yang didasarkan atas hak-hak warga negara.